Neuroanatomical and Neurocognitive Differences Between the Executive Functions in Child Sexual Offenders: A Systematic Review - Yaiza Ara-García; Manuel Martí-Vilar; Laura Badenes-Ribera; Francisco González-Sala (Brain Sciences)
Background/Objectives: Studies on executive functions in child sex offenders relate their findings to the presence of pedophilia, but they are not able to distinguish between paraphilia and abuse. It is therefore this lack of a distinction that leads us to complement the existing information. Thus, the purpose of this review is to find all available evidence on the neurocognitive and neuroanatomical differences in executive functions among pedophilic and non-pedophilic child sex offenders, and non-offender pedophiles. Methods: The present review, in accordance with the PRISMA statement, ran a systematic search of three databases (Web of Science, Scopus and ProQuest). This search identified 5697 potential articles, but only 16 studies met all the inclusion criteria. Most of the studies were conducted in Europe, using a cross-sectional design with a convenience sample. Results: The results showed alterations in frontal, temporal and parietal structures related to executive functions (e.g., response inhibition) in child sexual offenders, regardless of the presence of pedophilia. Conclusions: In summary, there are differences in brain structure underlying executive functions related to child sexual abuse, but not to pedophilia as such.